2012
DOI: 10.1175/jcli-d-11-00215.1
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Investigation of Wet and Dry Onset Modes in the North American Monsoon Core Region. Part I: A Regional Mechanism for Interannual Variability

Abstract: In this study the results of two regional fifth-generation Pennsylvania State University-NCAR Mesoscale Model (MM5) simulations forced at their boundaries with low-pass-filtered North American Regional Reanalysis (NARR) composite fields from which synoptic-scale variability was removed are presented. The filtered NARR data are also assimilated into the inner domain through the use of field nudging. The purpose of this research is to investigate wet and dry onset modes in the core region of the North American m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 48 publications
(48 reference statements)
2
10
0
Order By: Relevance
“…Water resources in the NAM region also are under increasing pressure from population growth, urban expansion, agricultural intensification [ Magaña and Conde , ; Liverman and Merideth , ; Douglas , ], a history of multidecadal droughts [ Sheppard et al ., ], and climate change [ Seager et al ., ; Diffenbaugh et al ., ]. As a result, improved understanding of the underlying mechanisms of the NAM has become a priority [ Higgins et al ., ; Barlow et al ., ; Higgins and Shi , ; Small , ; Berbery , ; Castro et al ., ; Mitchell et al ., ; Gutzler , ; Gochis et al ., ; Higgins and Gochis , ; Gutzler et al ., ; Castro et al ., ; Turrent and Cavazos , ], with increasing recognition of the controls exerted by the land surface [ Vivoni et al ., ; Zhu et al ., ; Méndez‐Barroso and Vivoni , ; Vivoni et al ., ; Forzieri et al ., ; Tang et al ., ; Vivoni , ; Mascaro et al ., ]. Recent studies have found strong ET‐P feedbacks, or precipitation recycling, in the NAM region [ Bosilovich et al ., ; Dominguez et al ., ; Hu and Dominguez , ; Feng and Houser , ], suggesting that simulation errors in ET fluxes may influence the accuracy of monsoon precipitation forecasts [ Koster et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Water resources in the NAM region also are under increasing pressure from population growth, urban expansion, agricultural intensification [ Magaña and Conde , ; Liverman and Merideth , ; Douglas , ], a history of multidecadal droughts [ Sheppard et al ., ], and climate change [ Seager et al ., ; Diffenbaugh et al ., ]. As a result, improved understanding of the underlying mechanisms of the NAM has become a priority [ Higgins et al ., ; Barlow et al ., ; Higgins and Shi , ; Small , ; Berbery , ; Castro et al ., ; Mitchell et al ., ; Gutzler , ; Gochis et al ., ; Higgins and Gochis , ; Gutzler et al ., ; Castro et al ., ; Turrent and Cavazos , ], with increasing recognition of the controls exerted by the land surface [ Vivoni et al ., ; Zhu et al ., ; Méndez‐Barroso and Vivoni , ; Vivoni et al ., ; Forzieri et al ., ; Tang et al ., ; Vivoni , ; Mascaro et al ., ]. Recent studies have found strong ET‐P feedbacks, or precipitation recycling, in the NAM region [ Bosilovich et al ., ; Dominguez et al ., ; Hu and Dominguez , ; Feng and Houser , ], suggesting that simulation errors in ET fluxes may influence the accuracy of monsoon precipitation forecasts [ Koster et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Daily 700 and 500 hPa winds, geopotential heights, and q and daily precipitable water (PW) were obtained from the National Center for Environmental Prediction (NCEP) North American Regional Reanalysis (NARR; Mesinger et al, ) and downloaded from the Earth System Research Laboratory Physical Sciences Division (https://www.esrl.noaa.gov/psd/data/gridded/data.narr.html). Despite some known limitations of NARR (Dominguez et al, ; Becker et al, ; Cerezo‐Mota et al, ), numerous studies have shown NARR representative when examining synoptic circulation and moisture across the study region (e.g., Dominguez et al, ; Dominguez and Kumar, ; Turrent and Cavazos, ; Doubler et al, ; Radhakrishna et al, ). We used a subset of daily NARR data that spanned from 85°W to 131°W longitude and 18°N to 49.5°N latitude.…”
Section: Datamentioning
confidence: 99%
“…noaa.gov/psd/data/gridded/data.narr.html). Despite some known limitations of NARR Becker et al, 2009;Cerezo-Mota et al, 2011), numerous studies have shown NARR representative when examining synoptic circulation and moisture across the study region (e.g., Turrent and Cavazos, 2012;Doubler et al, 2015;Radhakrishna et al, 2015). We used a subset of daily NARR data that spanned from 85 W to 131 W longitude and 18 N to 49.5 N latitude.…”
Section: Datamentioning
confidence: 99%
“…In general, winter/spring SST anomalies associated with El Niño/Southern Oscillation (ENSO) and subsequent summer rainfall in AZNM tend to be anti‐correlated (Gutzler and Preston, ; Higgins et al , ; Castro et al , ). Turrent and Cavazos () and Turrent and Cavazos () point to more regional scale SST forcing, and in particular, the regional land‐sea thermal contrast as the principal mechanism driving interannual variability in NAM onset. Clearly, these large‐ and smaller‐scale forcings are inter‐related.…”
Section: Background To Nam and Controlling Factorsmentioning
confidence: 99%